Semifluorinated Alkane Eye Drops for Treatment of Dry Eye Disease—A Prospective, Multicenter Noninterventional Study - Steven, Philipp (J Ocul Pharmacol Ther, 2015)
Purpose: Evaporation of the tear film is heavily discussed as one core reason for dry eye disease (DED). Subsequently, new artificial tear products are developed that specifically target this pathomechanism. Perfluorohexyloctane (F6H8, NovaTears(®)) from the family of semifluorinated alkanes is a novel substance that has been approved as a medical device, as a nonblurring wetting agent for the ocular surface. Methods: Thirty patients with hyperevaporative dry eye received F6H8 during a prospective, multicenter, observational 6-week study. Patients were advised to apply 1 drop 4 times daily in both eyes. Parameters assessed included best corrected visual acuity, intraocular pressure, Schirmer I test, tear fluid, tear film breakup time (TFBUT), corneal staining, meibum secretion, and Ocular Surface Disease Index (OSDI(©)). Results: From the 30 patients recruited, 25 completed the trial per protocol. Four patients discontinued F6H8 and 1 patient did not present for follow-up. F6H8 treatment led to significant reduction of corneal staining and significant increase of Schirmer I and TFBUT. In addition, OSDI score dropped significantly from a mean of 55 (±23.0) to 34 (±22.4). Visual acuity and ocular pressure did not change. Conclusions: This prospective observational study shows significant beneficial effects in patients suffering from evaporative DED, using F6H8 in all the relevant parameters tested. The decrease of the OSDI by a mean of 21 points was particularly remarkable and clearly exceeds minimal, clinical important differences for mild or moderate and severe disease. Overall, F6H8 (NovaTears) seems to be safe and effective in treating mild to moderate hyperevaporative DED.